Syria in a Torment: Key Actors and Geopolitical Intrigues - Oyosoro, Felix, Idongesit (My University, 2021)
Defined as the “worst humanitarian disaster since the end of the cold war,” the Syrian civil war has to date claimed heavy casualties, including over 8,000 documented killings of children under eighteen years of age. In a country of approximately 22 million people, the bloody and prolonged conflict has resulted in 7.6 million internally displaced persons and an additional 3.2 million refugees, as well as approximately 12.2 million people (more than 1 in 2 Syrians) in need of humanitarian aid to survive. This essay is an analysis of the Syrian conflict. Its aim is to depict and underline the various aspects of the conflict in Syria. The internal and external actors alongside the geopolitical intrigues and interests involved in this conflict shall be scrutinized. This essay thrives to rectify subsequent analytical mistakes of scholars who limit the conflict in Syria to one about a confrontation between Russia and the USA, or try to predict the conflict through that lens alone, simply because the most demonstrated rivalry about Syria as a geostrategic epiphenomena relies on the conflict between Iran and Saudi Arabia. Above and beyond the internal power struggle, the conflict has acquired the character of a proxy war in which international, regional and sub-national conflicts are fought out. The actors here treat the conflict as a zero-sum game, where success for one is automatically a defeat for the other. One bone of contention is the interpretation and enforcement of international norms, with the United States and other Western states backing the Syrian opposition while Russia, Iran and China support the Assad regime with trade and protection in the UN Security Council and, in the case of Russia, arms deliveries.Defined as the “worst humanitarian disaster since the end of the cold war,” the Syrian civil war has to date claimed heavy casualties, including over 8,000 documented killings of children under eighteen years of age. In a country of approximately 22 million people, the bloody and prolonged conflict has resulted in 7.6 million internally displaced persons and an additional 3.2 million refugees, as well as approximately 12.2 million people (more than 1 in 2 Syrians) in need of humanitarian aid to survive. This essay is an analysis of the Syrian conflict. Its aim is to depict and underline the various aspects of the conflict in Syria. The internal and external actors alongside the geopolitical intrigues and interests involved in this conflict shall be scrutinized. This essay thrives to rectify subsequent analytical mistakes of scholars who limit the conflict in Syria to one about a confrontation between Russia and the USA, or try to predict the conflict through that lens alone, simply because the most demonstrated rivalry about Syria as a geostrategic epiphenomena relies on the conflict between Iran and Saudi Arabia. Above and beyond the internal power struggle, the conflict has acquired the character of a proxy war in which international, regional and sub-national conflicts are fought out. The actors here treat the conflict as a zero-sum game, where success for one is automatically a defeat for the other. One bone of contention is the interpretation and enforcement of international norms, with the United States and other Western states backing the Syrian opposition while Russia, Iran and China support the Assad regime with trade and protection in the UN Security Council and, in the case of Russia, arms deliveries.
Keywords: Al Qaeda; Ammunitions; Civil War; Cold War; Conflict; Iran; ISIS; Nuclear Weapons; Russia; Syria